Autoimmunity against cytokines: Double strike in autoimmune disease, a historical perspective - Iván Insignares; Luis E. Rodríguez; Óscar Correa-Jiménez; Alberto Alfaro-Murillo; Laura Rincón-Arenas; Andrés Sánchez; Marlon Múnera (Biomédica: revista del Instituto Nacional de Salud)
Autoimmune responses are characterized by the development of antibodies and the activation of T lymphocytes against self-antigens. This leads to an effector immune response against tissues expressing antigens, which are later recognized by the host immune system. Host antigens attacked by antibodies are called “autoantigens” and are of different kinds, including receptors, enzymes, and channel proteins. The autoimmune response is potentiated by cytokines that mediate the activation of Th1, Th2, or Th17 lymphocytes. The released cytokines can also be recognized as autoantigens, meaning they can be targets of the autoimmune response. The effects of autoimmunity on cytokines or their receptors are diverse, and the mechanisms of this type of autoimmune response are discussed in this review.